2018
DOI: 10.1021/acs.jpca.7b12390
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Stability of the gem-Diol Forms in Imidazole Derivatives Containing Carbonyl Groups. Solid-State NMR and Single-Crystal X-ray Diffraction Studies

Abstract: The stability of gem-diol forms in imidazolecarboxaldehyde isomers was studied by solid-state nuclear magnetic resonance (ss-NMR) combined with single-crystal X-ray diffraction studies. These methodologies also allowed determining the factors governing the occurrence of such rare functionalization in carbonyl moieties. Results indicated that the position of the carbonyl group is the main factor that governs the generation of geminal diols, having a clear and direct effect on hydration, since, under the same ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…Similar shi values have been previously reported for water molecules in many different systems. 7,53,54 Particularly, Gul-E-Noor et al assigned proton resonances of water molecules in the range of d 1 H ¼ 15-4 ppm for Cu 3 (BTC) 2 MOF structures. 55,56 The main difficulty in studying the chemical functionalization of the ligand in the Cu(II) complex obtained in water is that single crystals for structural characterization could not be obtained.…”
Section: Solid-state Nmr Assignment In Cu(ii)-4pyridinecarboxaldehydementioning
confidence: 99%
See 1 more Smart Citation
“…Similar shi values have been previously reported for water molecules in many different systems. 7,53,54 Particularly, Gul-E-Noor et al assigned proton resonances of water molecules in the range of d 1 H ¼ 15-4 ppm for Cu 3 (BTC) 2 MOF structures. 55,56 The main difficulty in studying the chemical functionalization of the ligand in the Cu(II) complex obtained in water is that single crystals for structural characterization could not be obtained.…”
Section: Solid-state Nmr Assignment In Cu(ii)-4pyridinecarboxaldehydementioning
confidence: 99%
“…In particular, nitrogen heterocycles such as imidazole and pyridine molecules containing carbonyl or its hydrated groups known as gem-diols are widely used, due to their coordination properties, [1][2][3][4] especially in catalysis and environmental chemistry. Working with this kind of system is a challenge since the instability of gemdiol [5][6][7][8][9][10] creates uncertainty over the form of the ligand, hence careful characterization is particularly important. 9,[11][12][13][14] Taking into account the key role of NMR spectroscopy in characterizing the chemical structure of new compounds, copper and cobalt complexes containing this type of ligand are a challenge for this technique.…”
Section: Introductionmentioning
confidence: 99%
“…In organic synthesis, the attack of oxygen‐containing nucleophiles (e.g., H 2 O and OH − ) on the carbonyl group of aldehydes and ketones usually leads to an unstable gem ‐diol structure . Recently, stable gem ‐diol‐type species were identified in carbonyl‐containing organic compounds, such as formylpyridine and imidazole derivatives, which have 13 C signals in the range of 70–100 ppm. Thus, it is most likely that the ‐OH group of the open Sn site is involved in the nucleophilic attack on the carbonyl group of adsorbed [2‐ 13 C]acetone producing a gem ‐diol‐type species, which probably resonates at 76 ppm in the 13 C NMR spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…[18] To explore the interaction of alcohol with the Sn site, 13 Clabelled [2-13 C]isopropanol was deliberately adsorbed on Sn-b zeolite.Asshown in the 13 CNMR spectrum ( Figure S2), both the physisorbed isopropanol and isopropyl alkoxy species generated by the dehydration of isopropanol are observed on the zeolite,which produce methenyl signals at 69 and 72 ppm, respectively.I no rganic synthesis,t he attack of oxygencontaining nucleophiles (e.g., H 2 Oand OH À )onthe carbonyl group of aldehydes and ketones usually leads to an unstable gem-diol structure. [19] Recently,s table gem-diol-type species were identified in carbonyl-containing organic compounds, such as formylpyridine [20] and imidazole [21] derivatives,which have 13 Cs ignals in the range of 70-100 ppm. Thus,i ti sm ost likely that the -OH group of the open Sn site is involved in the nucleophilic attack on the carbonyl group of adsorbed [2- 13 C]acetone producing a gem-diol-type species,w hich probably resonates at 76 ppm in the 13 CNMR spectrum.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Due to ambiguous analytical data of iprGlu, which is present as the aldehyde as well as its stable hydrate from, it was converted completely into its stable hydrate form under the addition of water, which subsequently crystallized as white solid [31]. Despite the fact that hydrates of carbonyls, the so-called gem-diols, are generally not stable and can therefore not be isolated, there are some exceptions [39][40][41]. In this case, the crystalline gem-diol structure was studied by Stefanowicz et al [31], who also demonstrated that the hydrate converts back to the aldehyde in solution, therefore not hampering further reactions of the aldehyde group.…”
Section: Synthesis Of Iprglu As Reactive Carbohydrate Intermediatementioning
confidence: 99%